Microfluidic Device for the Selective Chemical Stimulation of Neurons and Characterization of Peptide Release with Mass Spectrometry - Croushore, Callie A. (American Chemical Society, 2012)
[Image: see text] Neuropeptides are synthesized in and released from neurons and are involved in a wide range of physiological processes, including temperature homeostasis, learning, memory, and disease. When working with sparse neuronal networks, the ability to collect and characterize small sample volumes is important as neurons often release only a small proportion of their mass-limited content. Microfluidic systems are well suited for the study of neuropeptides. They offer the ability to control and manipulate the extracellular environment and small sample volumes, thereby reducing the dilution of peptides following release. We present an approach for the culture and stimulation of a neuronal network within a microfluidic device, subsequent collection of the released peptides, and their detection via mass spectrometry. The system employs microvalve-controlled stimulation channels to selectively stimulate a low-density neuronal culture, allowing us to determine the temporal onset of peptide release. Released peptides from the well-characterized, peptidergic bag cell neurons of Aplysia californica were collected and their temporal pattern of release was characterized with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. We show a robust difference in the timing of release for chemical solutions containing elevated K(+) (7 ± 3 min), when compared to insulin (19 ± 7 min) (p < 0.000 01).